Problematika Penggunaan Artificial Intelligence pada Mahasiswa Universitas PGRI Jombang - Masruchan; Nurmilah, Rifa (SAFE-Network, 2024)
This article discusses the challenges of using artificial intelligence among students at Universitas PGRI Jombang. In this context, this study examines the use of artificial intelligence, the risk of dependency, and its impact on the development of personal property rights, especially critical and contextual analysis. All of this shows that the use of artificial intelligence among students at Universitas PGRI Jombang faces many problems, including plagiarism, decreased student criticism, and decreased student performance. This study uses observation interview methods and studies among students at Universitas PGRI Jombang. This article provides an overview of the challenges of integrating AI into education and highlights the need for effective research methods to provide maximum benefits without damaging the development of students' intellectual and skill skills.